Кинетика процессов осаждения пленок поликремния, легированного кислородом в процессе роста - Nalivaiko, O. Yu.; Тurtsevich, A. S. (PE "Politekhperiodika", Book and Journal Publishers, 2012)
The influence of deposition conditions on composition of in-situ oxygen doped polysilicon films has been investigated. A kinetic model of adsorption-deposition process using concentrated silane and nitrous oxide has been developed. The range of optimal ratios of silane and nitrous oxide flows and deposition temperature, which provide the acceptable deposition rate, thickness uniformity, controllability of oxygen content in films and conformal deposition, have been determined.